BANKING CRISES: EMPIRICAL EVIDENCE OF IRANIAN BANKERS - Mandi Salehi; Ali Mansouri (Indonesian Management and Accounting Research, 2009)
"Bank" is a term people use broadly to refer to many different types of financial institutions Banks generally, accept deposits and make loans. Deposits are money people leave in an institution with the understanding that they can get it back at any time or at an agreed-upon future time. A loan is money let out to a borrower to be generally paid back with interest. This action of taking deposits and making loans is called financial intermediation. In the view of the fact, banks like other institutions looking for benefit and income. This survey shows after interfering Iranian government to banking sector the going concern of Iranian banks became sustainable. This condition create some problems to Iranian economic, especially it caused higher level of inflation in Iran.Key Words: Bank crises, Survival, Inflation